Studi Mekanisme Sedimentasi Formasi Dolokapa, Gorontalo - Tedy Harianto Salama; Sri Maryati; Intan Noviantari Manyoe (Jambura Geoscience Review, 2021)
The Dolokapa Formation is a sedimentary rock formation formed in a deep-sea depositional environment with a fairly complex level of deformation and tectonic arrangement. Analysis of the sedimentation mechanism is carried out to determine how much tectonic influence on the mechanisms that occur in a depositional environment and the variations in the sedimentation mechanism formed. Research on the sedimentation mechanism needs to be carried out to determine the history of the formation of Gorontalo sedimentary rocks, especially in the Dolokapa Formation which was formed during the Miocene. The purpose of this study is to know the mechanisms of deep-marine sedimentation based on the identification of lithological characteristics, layer stacking patterns, and sedimentary structures. The method used was measuring sections using a range of ropes divided into four measurement paths. After that, a correlation was performed based on the genesis of deep marine formation. Based on the results of processing and analysis of the data, obtained units of lithology that insertion silty-clay, and the sandstone graining insertion of silt. In vertical succession, the layering pattern formed generally thickens upwards which describes the energy of the depositional currents. The sedimentary structure consists of rip up-clast, parallel lamination, graded bedding, convolute, slump, and trace fossils of nereites trace fossils of nereites that characterize the sedimentation of traction currents and turbidite currents in the deep-sea environment. The sedimentation mechanism formed is the traction current mechanism which is a further development of turbidite current and high-low concentration turbidity current mechanism that occurs slowly on a suspension-controlled grain. The stratigraphic relationship of the rock units in the research area is aligned based on the genesis formation that is located in the setting of the deep marine.